Nanostructured Lipid Carriers (NLCs) for Oral Peptide Drug Delivery: About the Impact of Surface Decoration - Iram Shahzadi; Andrea Fürst; Patrick Knoll; Andreas Bernkop-Schnürch (MDPI AG, 2021)
This study was aimed to evaluate the impact of surfactants used for nanostructured lipid carriers (NLCs) to provide enzymatic protection for incorporated peptides. Insulin as a model peptide was ion paired with sodium dodecyl sulfate to improve its lipophilicity. Three NLC formulations containing polyethylene glycol ester (PEG-ester), polyethylene glycol ether (PEG-ether), and polyglycerol ester (PG-ester) surfactants were prepared by solvent diffusion method. NLCs were characterized regarding particle size, polydispersity index, and zeta potential. Biocompatibility of NLCs was assessed on Caco-2 cells via resazurin assay. In vitro lipolysis study was performed using a standard lipid digestion method. Proteolytic studies were performed in simulated gastric fluid containing pepsin and simulated intestinal fluid containing pancreatin. Lipophilicity of insulin in terms of log Poctanol/water was improved from −1.8 to 2.1. NLCs were in the size range of 64-217 nm with a polydispersity index of 0.2-0.5 and exhibited a negative surface charge. PG-ester NLCs were non-cytotoxic up to a concentration of 0.5%, PEG-ester NLCs up to a concentration of 0.25% and PEG-ether NLC up to a concentration of 0.125% (w/v). The lipolysis study showed the release of >90%, 70%, and 10% of free fatty acids from PEG-ester, PG-ester, and PEG-ether NLCs, respectively. Proteolysis results revealed the highest protective effect of PEG-ether NLCs followed by PG-ester and PEG-ester NLCs for incorporated insulin complex. Findings suggest that NLCs bearing substructures less susceptible to degrading enzymes on their surface can provide higher protection for incorporated peptides toward gastrointestinal proteases.